Kapabilitas Manajerial Dinamik Dan Kapasitas Organisasi Untuk Berubah Anteseden Dan Konsekuensi Dalam Meningkatkan Kinerja Organisasi Studi Empiris Pada Perguruan Tinggi Pelayaran Niaga - F. Pambudi Widiatmaka; Suherman Suherman; Sukrisno Sukrisno; Anugrah Nur Prasetyo (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to build a conceptual model for improving organizational performance. The proposed model is based on dynamic managerial capabilities and organizational capacity to change. A structural study methodology was adopted using 200 samples taken from managers at Pelayaran Niaga colleges in Indonesia and data collected through questionnaires, to test the models and hypotheses in this study, the authors used Amos 25 as a data analysis tool. The results of this study indicate that there is a strategic path to improve organizational performance in public organizations, namely educational organizations at Pelayaran Niaga colleges in Indonesia, namely through a dynamic managerial ability path and then organizational capacity to change which can further increase organizational performance. This study has limitations such as not being able to define specifically about dynamic managerial abilities. In addition, the sample used is only limited to the Merchant Shipping College to represent public organizations. The results of this study are applied to strengthen the theory of change management theory of dynamic capabilities and organizational behavior. In addition, this research is also able to contribute to a practical level to provide recommendations for top managers, middle managers and lower managers in public organizations in order to be able to provide a form of performance improvement. organization based on organizational change and dynamic capabilities possessed by each manager in public organization.